Unsteady MHD Flow of Some Nanofluids Past an Accelerated Vertical Plate Embedded in a Porous Medium - Abid, Hussanan; Khan, Ilyas; Hasmawani, Hashim; Muhammad Khairul Anuar, Mohamed; Nazila, Ishak; Norhafizah, Md Sarif; Mohd Zuki, Salleh (Penerbit Universiti Teknologi Malaysia, 2016)
The present paper deals with the unsteady magnetohydrodynamics (MHD) flow and heat transfer of some nanofluids past an accelerating infinite vertical plate in a porous medium. Water as conventional base fluid containing three different types of nanoparticles such as copper (Cu), aluminum oxide (Al2O3) and titanium oxide (TiO2) are considered. By using suitable transformations, the governing partial differential equations corresponding to the momentum and energy are converted into linear ordinary differential equations. Exact solutions of these equations are obtained with the Laplace Transform method. The influence of pertinent parameters on the fluid motion is graphically underlined. It is found that the temperature of Cu-water is higher than those of Al2O3-water and TiO2-water nanofluids.